1997
DOI: 10.1210/mend.11.7.9948
|View full text |Cite
|
Sign up to set email alerts
|

The ERR-1 Orphan Receptor Is a Transcriptional Activator Expressed During Bone Development

Abstract: We studied the expression of estrogen-related receptor ERR-1 during mouse embryonic development. ERR-1 mRNA is present in bones formed by both the endochondral and intramembranous routes, and the onset of its expression coincides with bone formation. By RT-PCR experiments, we found that ERR-1, but not the related receptor ERR-2, is expressed in osteoblastic osteosarcoma cell lines as well as in primary osteoblastic cell populations derived from normal human bone. By gel shift analysis we found that ERR-1 binds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(50 citation statements)
references
References 37 publications
2
47
0
Order By: Relevance
“…ERRa also down regulates the SV40 major late promoter (Wiley et al, 1993;Johnston et al, 1997). In contrast, we have demonstrated that ERRadependent transactivation through the SFRE is cellspeci®c (Bonnelye et al, 1997a). Indeed, cell lines such as HeLa or NB-E support ERRa-induced SFREdependent transcriptional regulation whereas others like HepG2 or COS1 do not.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…ERRa also down regulates the SV40 major late promoter (Wiley et al, 1993;Johnston et al, 1997). In contrast, we have demonstrated that ERRadependent transactivation through the SFRE is cellspeci®c (Bonnelye et al, 1997a). Indeed, cell lines such as HeLa or NB-E support ERRa-induced SFREdependent transcriptional regulation whereas others like HepG2 or COS1 do not.…”
Section: Introductionmentioning
confidence: 64%
“…Analysis of the sequence of this promoter reveals the existence of a perfect consensus SF-1 responsive element (SFRE; Wilson et al, 1993). As we have recently demonstrated, this site is also responsible for binding and activation by another nuclear orphan receptor, namely ERRa (Bonnelye et al, 1997a). As a ®rst step in evaluation of the signi®cance of this site, we decided to compare the sequence of the human version of the TRa promoter with the rat version isolated by Lazar et al (1994).…”
Section: Binding Of Erra On the Tra Promotermentioning
confidence: 99%
See 3 more Smart Citations